HUBUNGAN PENGETAHUAN IBU TENTANG RISIKO CEDERA DENGAN PENCEGAHAN CEDERA BERULANG PADA ANAK USIA TODDLER - Keness Purnanin Grat (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Toddlers experience progress in motor development, exploration, high curiosity, and do not understand the dangers, so they are at risk of injury that can affect their growth and development. Mothers need to have good knowledge about the risk of injury to children to prevent injury. This study aims to determine the relationship between a mother's knowledge about the risk of injury and the prevention of repetitive injuries in toddlers. This study used a descriptive correlation design and a cross-sectional approach. The research sample was 205 respondents using a proportional purposive sampling technique. The analysis used is the chi-square test. Most of the mothers had good knowledge (72.7%) and Most of the prevention of repetitive injuries is good (65,4%). The results of statistical tests showed that there was a relationship between a mother's knowledge of the risk of injury and the prevention of repetitive injuries in toddlers (p-value 0.000: alpha 0.05). Mother's knowledge about the risk of injury can affect the prevention of repetitive injuries in toddlers. This study suggests that mothers continue to increase their knowledge about the risk of injury to toddlers so that the prevention of repeated injuries by mothers is good.